Purely Organic Microparticles Showing Ultralong Room Temperature Phosphorescence - Thomas, Heidi; Fries, Felix; Baerschneider, Toni; Kroll, Martin; Vavaleskou, Thaleia; Reineke, Sebastian; Gmelch, Max (ACS Omega, 2021)
Currently, organic phosphorescent particles are heavily used in sensing and imaging. Up to now, most of these particles contain poisonous and/or expensive metal complexes. Environmentally friendly systems are therefore highly desired. A purely amorphous system consisting of poly(methyl methacrylate) particles with incorporated N,N,N',N'-tetrakis(4-carboxyphenyl)benzidine emitter molecules is presented in this work. Single particles with sizes between 400 and 840 nm show-depending on the environment-bright fluorescence and phosphorescence. The latter is observed when oxygen is not in the proximity of the emitting dye molecules. These particles can scavenge singlet oxygen, which is produced during the photoexcitation process, by incorporating it into the polymer matrix. This renders their use to be unharmful for the surrounding matter with possible application in marking schemes for living bodies.